2023
DOI: 10.7150/thno.78639
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and responsive biomaterials in osteoarthritis

Abstract: Osteoarthritis (OA) is a degenerative disease characterized by loss of articular cartilage and chronic inflammation, involving multiple cellular dysfunctions and tissue lesions. The non-vascular environment and dense cartilage matrix in the joints tend to block drug penetration, resulting in low drug bioavailability. There is a desire to develop safer and more effective OA therapies to meet the challenges of an aging world population in the future. Biomaterials have achieved satisfactory results in improving d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 203 publications
0
32
0
Order By: Relevance
“…Triamcinolone acetonide injection (TA IR) slightly decreased the abundances of CD68-and iNOS-positive cells, which was accompanied by a low level of CD206 expression in advantageous in the treatment of OA. 58,59 Taken together, these results demonstrated that TA-NM@Lip could effectively orchestrate macrophages and fibroblast phenotypes in osteoarthritic joints. TA-NM@Lip Leads to Complete Joint Pain Relief and Inhibits Synovitis in an Experimental Model of OA Pain.…”
Section: Ta-nm@lip Effectively Reprograms the Phenotype Of Both M1 Ma...mentioning
confidence: 60%
See 1 more Smart Citation
“…Triamcinolone acetonide injection (TA IR) slightly decreased the abundances of CD68-and iNOS-positive cells, which was accompanied by a low level of CD206 expression in advantageous in the treatment of OA. 58,59 Taken together, these results demonstrated that TA-NM@Lip could effectively orchestrate macrophages and fibroblast phenotypes in osteoarthritic joints. TA-NM@Lip Leads to Complete Joint Pain Relief and Inhibits Synovitis in an Experimental Model of OA Pain.…”
Section: Ta-nm@lip Effectively Reprograms the Phenotype Of Both M1 Ma...mentioning
confidence: 60%
“…TA-NM@Lip group resulted in the lowest expression of vimentin, VCAM1, and VEGF among all of the TA-treated groups, suggesting the transformation of activated SFs to the deactivated SFs. Compared with conventional drug delivery systems, nanoparticle-based targeted drug delivery systems can not only prolong the joint retention time of drugs but also exhibit higher tissue and cell specificity, which may be advantageous in the treatment of OA. , Taken together, these results demonstrated that TA-NM@Lip could effectively orchestrate macrophages and fibroblast phenotypes in osteoarthritic joints.…”
Section: Resultsmentioning
confidence: 86%
“…However, traditional systemic or intra-articular medication is often associated with systemic side effects, limited drug accumulation, and short residence times in the affected area . Therefore, development of a sustained drug delivery system is crucial to achieve effective and prolonged treatment of cartilage lesions and meniscal tears . Phosphatidylcholines (PCs), which are abundant in cartilage and synovial fluid, are phospholipids that provide lubrication at physiological levels under high pressures within joints .…”
Section: Introductionmentioning
confidence: 99%
“…16 Therefore, development of a sustained drug delivery system is crucial to achieve effective and prolonged treatment of cartilage lesions and meniscal tears. 17 Phosphatidylcholines (PCs), which are abundant in cartilage and synovial fluid, are phospholipids that provide lubrication at physiological levels under high pressures within joints. 18 Meanwhile, PCs are ideal candidates for delivering drugs or other therapeutic agents due to their ability to facilitate tissue/ cell targeting, enhance drug efficacy, and improve bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] In response to external stimuli, these multifunctional biomaterial scaffolds release chemotherapeutic agents or immunomodulators in situ to cure bone tumors. [24][25][26][27] With the participation of functional biomaterial scaffolds, metastasis and recurrence of bone tumors can be effectively prevented while promoting bone repair at the defect site (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%